Analisis Pengabaian Batasan Interaksi Mahram Mu’aqqat Dalam Film Ipar Adalah Maut 2024 - Edison Edison; Nola Fibriyani; Wazni Wazni (Tazkir: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2026)
The Muslim family sphere must maintain the manners of mahrams. Neglect of mahram manners is the doorway to adultery. This topic was chosen because of the rampant adultery in the family sphere, both those that are revealed to the public, and those that are not published. This research method is media content analysis using explorative techniques. The data obtained was analyzed qualitatively. This research analyzes the content of some neglect of mahram manners that trigger adultery in the film ''Ipar adalah Maut''. Some of the mahram manners that are violated include the toleration of brothers-in-law going together in one vehicle. Then, the sister-in-law who lives in the same house, remains at home, when only the brother-in-law (husband of the older sister) is at home.The older sister (wife's) testamentary that while traveling out of town the sister-in-law should serve the brother-in-law became a carelessness that was misused, leading to adultery. In order to prevent adultery in the family sphere, the following mahram manners must be observed. The manners of mahrams include not being alone together; not traveling or traveling tete a tete; and keeping aurat. The results of this study serve as a fundamental guide for each family member in obeying the manners of mahrams so as not to be trapped in the trap of adultery in the family sphere. The strength of this research is the ability to explore the distinctive perspectives of the movie “Ipar is Death” to be used as an agitational medium to warn about the dangers of ignoring mahram manners.